DIMENSIUNI ALE INTELIGENŢEI APRECIATIVE: STILUL APRECIATIV - USM ADMIN (Moldova State University, 2010)
In this paper a theoretical analysis on the intelligence has been carried out. The appreciative style is an important element in the structure of the appreciative intelligence. The classification of events as constructive or destructive, making plans for the future, the existence of "a positive thinking" - all are closely related to the personal appreciative style.